Critical analysis of Imam Al-Mawardi’s Political and Military Maneuverers: امام الماوردی کی عسکری وسیاسی حکمت عملیوں کا علمی وتحقیقی جائزہ - ullah, Dr. Inayat; Shoaib, Dr. Muhammad (Al Khadim Research Journal of Islamic Culture and Civilization, 2025)
Islam is the religion of peace and it’s the only religion from Allah Almighty. It is the predominant religion, Allah Almighty spread this religion unprecedentedly all over the world. In the period of savagery, rapine and killing was considered as a sign of glory and arrogance, people fought for years for frivolous and insignificant matters and they became bloodsuckers of each other. Islamic teachings and principles annulled all such barbaric practices, however, to completely abolish internal and external riots, Prophet (SAW) and his followers were commanded to engage in Ghazwat and battles. With the grace of Almighty Allah as well as leadership of Prophet (SAW), Muslims won all those battles. Due to great political, military and defensive tactics of Prophet (SAW), Allah Almighty bestowed Muslims with great successes. Along with other subjects, a chapter named “Al-AMARAT-AL-JEHAD”is included by Al-Mawardi in his famous book “AL-AHKAM-ALـ SULTANIA”, which include: military management, commanders' as well as military soldiers’ responsibilities and their behavior toward enemies. In this research we are discussing Al-Mawardi’s concepts with details.